Diagnostic accuracy of blood tests of inflammation in paediatric appendicitis: a systematic review and meta-analysis - Fawkner-Corbett, D; Hayward, G; Alkhmees, M; Van Den Bruel, A; Ordóñez-Mena, JM; Holtman, GA (BMJ Publishing Group, 2022)
Objective: Possible childhood appendicitis is a common emergency presentation. The exact value of blood tests is debated. This study sought to determine the diagnostic accuracy of four blood tests (white cell count (WCC), neutrophil(count or percentage), C reactive protein (CRP) and/or procalcitonin) for childhood appendicitis. Design: A systematic review and diagnostic meta-analysis. Data sources included MEDLINE, EMBASE, Central, Web of Science searched from inception-March 2022 with reference searching and authors contacted for missing/unclear data. Eligibility criteria was studies reporting the diagnostic accuracy of the four blood tests compared to the reference standard (histology or follow-up). Risk of bias was assessed (QUADAS-2), pooled sensitivity and specificity were generated for each test and commonly presented cut-offs. To provide insight into clinical impact, we present strategies using a hypothetical cohort. Results: 67 studies were included (34 839 children, 13 342 with appendicitis), all in the hospital setting. The most sensitive tests were WCC (≥10 000 cells/µL, 53 studies sensitivity 0.85 (95% CI 0.80 to 0.89)) and absolute neutrophil count (ANC) (≥7500 cells/µL, five studies sensitivity 0.90 (95% CI 0.85 to 0.94)). Combination of WCC or CRP increased sensitivity further(≥10 000 cells/µL or ≥10 mg/L, individual patient data (IPD) of 6 studies, 0.97 (95% CI 0.93 to 0.99)). Applying results to a hypothetical cohort(1000 children with appendicitis symptoms, of whom 400 have appendicitis) 60 and 40 children would be wrongly discharged based solely on WCC and ANC, respectively, 12 with combination of WCC or CRP. The most specific tests were CRP alone (≥50 mg/L, 38 studies, specificity 0.87 (95% CI 0.80 to 0.91)) or combined with WCC (≥10 000 cells/µL and ≥50 mg/L, IPD of six studies, 0.93 (95% CI 0.91 to 0.95)). Conclusions: The best performing single blood tests for ruling-out paediatric appendicitis are WCC or ANC; with accuracy improved combining WCC and CRP. These tests could be used at the point of care in combination with clinical prediction rules. We provide insight into the best cut-offs for clinical application. PROSPERO registration number: CRD42017080036